2016
DOI: 10.1371/journal.pgen.1006050
|View full text |Cite
|
Sign up to set email alerts
|

NPR-9, a Galanin-Like G-Protein Coupled Receptor, and GLR-1 Regulate Interneuronal Circuitry Underlying Multisensory Integration of Environmental Cues in Caenorhabditis elegans

Abstract: C. elegans inhabit environments that require detection of diverse stimuli to modulate locomotion in order to avoid unfavourable conditions. In a mammalian context, a failure to appropriately integrate environmental signals can lead to Parkinson’s, Alzheimer’s, and epilepsy. Provided that the circuitry underlying mammalian sensory integration can be prohibitively complex, we analyzed nematode behavioral responses in differing environmental contexts to evaluate the regulation of context dependent circuit reconfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Many of these unc-42- dependent neuropeptides and neuropeptide receptors have been previously shown to be involved in locomotory behavior, and we found that these behavioral defects match subsets of the defects observed in unc-42 mutants. For example, animals lacking flp-18, nlp-15, npr-9, and npr-11 display decreased backwards motion (i.e., decreased reversals) ( Bhardwaj et al, 2018 ; Campbell et al, 2016 ; Chalasani et al, 2010 ; Yemini et al, 2013 ), thereby phenocopying the unc-42 defects that we have described here ( Figure 2 ). Among these, flp-18 and npr-11 are expressed in command interneurons that are responsible for backward locomotion, and we found their expression to be unc-42 dependent in these neurons ( Figure 6C, K ).…”
Section: Resultsmentioning
confidence: 59%
“…Many of these unc-42- dependent neuropeptides and neuropeptide receptors have been previously shown to be involved in locomotory behavior, and we found that these behavioral defects match subsets of the defects observed in unc-42 mutants. For example, animals lacking flp-18, nlp-15, npr-9, and npr-11 display decreased backwards motion (i.e., decreased reversals) ( Bhardwaj et al, 2018 ; Campbell et al, 2016 ; Chalasani et al, 2010 ; Yemini et al, 2013 ), thereby phenocopying the unc-42 defects that we have described here ( Figure 2 ). Among these, flp-18 and npr-11 are expressed in command interneurons that are responsible for backward locomotion, and we found their expression to be unc-42 dependent in these neurons ( Figure 6C, K ).…”
Section: Resultsmentioning
confidence: 59%
“…Restricted expression in cholinergic motor neurons (VNC) 71 Punc-47 All GABAergic neurons 66 Pmyo-3 Muscles Podr-2 (16) SMD, RME 34 Plgc-55 SMD, IL1, AVB, RMD, neck muscles 33 Pgcy-28.d AIA 72 Plim-4(s) (lim-4 promoter fragment from -3328 to -2174 upstream of start) RIV 33 Pnpr-9 AIB 73 Podr-2 (18) RIG, SMB 34 Posm-6 ADE, amphid neurons, AQR, CEM, CEP, HOA, HOB, IL1, IL2, OLL, OLQ, PDE, phasmid neurons. 74…”
Section: Promoter Expression Referencesmentioning
confidence: 99%
“…Although a number of studies have highlighted the neurons, molecules, and circuits that are required for the reversal behavior in C. elegans ( Chalfie et al, 1985 ; Kaplan and Horvitz, 1993 ; Hart et al, 1995 ; Maricq et al, 1995 ; Y. Zheng et al, 1999 ; Brockie et al, 2001 ; Zhao et al, 2003 ; Alkema et al, 2005 ; Gray et al, 2005 ; Cohen et al, 2009 ; Piggott et al, 2011 ; Campbell et al, 2016 ), most of these studies were focused on the reversal frequency. The role of neurons in regulating reversal length has to date been elaborated in a single previous study involving laser ablation of neurons ( Gray et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%